2019
DOI: 10.1155/2019/2985956
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone Prevents H2O2-Induced BRL-3A Cell Oxidative Damage through Activation of PI3K/Akt Pathways rather than MAPK Pathways

Abstract: Dehydroepiandrosterone (DHEA) is a popular dietary supplement that has well-known benefits in animals and humans, but there is not enough information about the mechanisms underlying its effects. The present study aimed at investigating these mechanisms through in vitro experiments on the effects of DHEA on rat liver BRL-3A cells exposed to oxidative stress through H2O2. The findings showed that DHEA increased the antioxidant enzyme activity, decreased ROS generation, and inhibited apoptosis in H2O2-treated cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In another study using BLA3A cells, it was reported that androgen had a protective effect on H 2 O 2 treated cells that experienced oxidative stress. This protective effect was mediated through the PI3K-AKT pathway and was reversed in the presence of flutamide [26]. Rossetti et al, 2017, summarized that castration of male mice reduced skeletal muscle P-AKT (Ser-473) and P-mTOR (Ser-2448) level, along with skeletal muscle protein synthesis and this effect was reversed upon exogenous administration of androgen to the to the castrated mice [27].…”
Section: Resultsmentioning
confidence: 99%
“…In another study using BLA3A cells, it was reported that androgen had a protective effect on H 2 O 2 treated cells that experienced oxidative stress. This protective effect was mediated through the PI3K-AKT pathway and was reversed in the presence of flutamide [26]. Rossetti et al, 2017, summarized that castration of male mice reduced skeletal muscle P-AKT (Ser-473) and P-mTOR (Ser-2448) level, along with skeletal muscle protein synthesis and this effect was reversed upon exogenous administration of androgen to the to the castrated mice [27].…”
Section: Resultsmentioning
confidence: 99%
“…Information regarding the influence of sex hormones on the p38 MAPK pathway is controversial. 39 , 40 Choosing only male animals eliminated the potential effects of sex on our results while making the study more homogeneous. However, this remains a broad topic, and further studies wholly dedicated to it could be very useful.…”
Section: Discussionmentioning
confidence: 99%